Etiological aspects of chronic heart failure on the background of overweight and obesity - Р. P. Bidzilya (Patologìâ)
In Ukraine, the number of patients with clinically manifested chronic heart failure (CHF) could reach 2 million, which corresponds to the prevalence of the disease in the Russian federation (5% of the adult population). The most important etiologic factors of CHF are coronary artery disease and arterial hypertension (AH) (especially in combination with diabetes mellitus and obesity). Recently, the role of AH in the development of CHF is progressively growing, the risk increases proportionately to degree of AH.